Land Characteristics of Batang Pelepat Watershed in Bungo District, Jambi - Sunarti Sunarti (UNIVERSITY OF LAMPUNG, 2010)
Land Characteristics of Batang Pelepat Watershed In Bungo District, Jambi (Sunarti): Land characteristics describe biophysics characteristics of watershed. But, land has been used for economic oriented. The objective of this research is to identify land characteristics of Batang Pelepat watershed. Data collection was carried out by survey based on land unit map and analyzed by descriptive analysis. The results showed that land in Batang Pelepat watershed consist of 23 land units and some land use types (forest, rubber and oil palm farming, settlement and shrub), soil parent materials variously (alluvium, granite, tuff andesite, basalt, and clay rock), soil depth ranges from 88 to 160 cm and soil texture is classified moderate fine to fine. Lands were dominated by slope of >15–30% and >45–65% and dystrudepts of soil group with soil fertility level very low to low because its pH about 3.80-6.20, base saturation about 7.86-32.79% and P- available about 2.80-25.00 ppm. Various land use has also caused different erosion and permeability levels.